TTHE IMPLEMENTATION OF MATCHING GAMES TO IMPROVE INDONESIAN LEARNING OUTCOMES FOR THE FIRST-GRADE STUDENTS AT SDN 1 CRJ - Niken Yulianah; Winarsih Winarsih; Uswati Solehah; Endang Sri Maruti; Nico Irawan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The low Indonesian learning outcomes of the first-grade students at SDN 1 CRJ is caused by the implementation of teacher-centered learning methods like the lecture method. To overcome it, the Classroom Action Research in this paper applies the Matching Games game method to students. This paper reports an improvement of studentsâ€™ learning outcomes in reading and writing Indonesian learning subjects in chapter 5 of "Teman Baru" with the entitled theme of "Bersikap Baik terhadap Teman" through the Matching Games method. There were three cycles of CAR applied to 12 students, which contains the planning, action, observation, and reflection stages for each cycle. The data analysis technique used in the research was descriptive, which compared cross-cycle test scores with indicators of success. The results indicate that the average score of studentsâ€™ learning outcomes in cycle I was 66.66 with only 50% of students who are able to achieve the learning objectives. Whereas in cycle II it was 80.83 with 90% of students who achieve the learning objectives. Based on the research results explained previously, the researcher concludes the results of Indonesian learning outcomes in reading and writing that students can be improved by applying the Matching Games method for elementary students at grade 1.Â